Single Molecule Analysis : Methods and Protocols - Peterman, Erwin J. G. (Methods in Molecular Biology, 2018)
The aim of this volume is to provide a broad overview of single-molecule approaches applied to biomolecules. Chapters in Single Molecule Techniques: Methods and Protocols, Second Edition detail the most widely used single-molecule techniques, such as DNA, DNA-binding proteins, motor proteins, and are becoming commonplace in molecular biophysics, biochemistry, and molecular and cell biology. Written in the highly successful Methods in Molecular Biology series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Single Molecule Analysis: Methods and Protocols, Second Edition aims to be useful to many researchers, inspire them and help them to go single molecule.